Effects of trapping number on biopolymer flooding recovery of carbonate reservoirs - AL-SHALABI Emad W. (Petroleum Exploration and Development, 2022)
The effects of trapping number on enhanced oil recovery by schizophyllan biopolymer flooding in carbonate reservoirs were investigated by running several 1D simulations using measured reservoir rock and fluid data. Sensitivity analysis was performed on different uncertain parameters to history match the oil recovery obtained in the core flooding experiment. These parameters include inaccessible pore volume (IPV), biopolymer adsorption, permeability reduction factor, shear rate coefficient, hardness of injection water, and trapping number. The IPV, biopolymer adsorption, permeability reduction factor, shear rate coefficient and hardness of injection water have negligible effects on oil recovery by biopolymer flooding. Also, history matching of oil recovery data was not possible when these parameters were varied within their typical range of values. When trapping number effect was considered through capillary desaturation curve (CDC), residual oil saturation was reduced from 25.1% without considering its effect or under low trapping number to 10.0%, and the fitting effect for recovery was better. Therefore, we can't neglect the trapping number effect during biopolymer flooding simulation in the carbonate reservoirs.